Metabolizm bilirubiny i jego znaczenie w patogenezie zespołów Rotora oraz Dubina i Johnsona - aktualny stan wiedzy - Lipiński, Patryk; Więcek, Sabina; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Authors present the prevailing knowledge about bilirubin metabolism and its implications in Rotor and Dubin-Johnson syndromes.